2015
DOI: 10.3402/gha.v8.29267
|View full text |Cite
|
Sign up to set email alerts
|

‘We are looked down upon and rejected socially’: a qualitative study on the experiences of trafficking survivors in Nepal

Abstract: BackgroundThe successful reintegration of sexual trafficking survivors into Nepalese society is challenging. This paper aims to explore the trafficking process, abuses faced during sexual slavery,and the challenges faced by women and girl survivors for successful reintegration.MethodThis exploratory study used qualitative methods to identify that poverty, illiteracy, lack of opportunities, and varied social stigma initiate the victimization process, and continuity of this vicious circle increases the risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…This environment appears to help survivors begin to view themselves as skilled professionals. Research with survivors of trafficking for sexual exploitation has found that a key to successful reintegration is reconstruction of the identity away from being a sexual object (Dahal et al, 2015). Participating in a healthy working environment after being trafficked ‘reclaims the experience of work and turns it into an experience of self-sufficiency and accomplishment’ for survivors (Brennan, 2014: 164).…”
Section: Approach To Core Skills Developmentmentioning
confidence: 99%
“…This environment appears to help survivors begin to view themselves as skilled professionals. Research with survivors of trafficking for sexual exploitation has found that a key to successful reintegration is reconstruction of the identity away from being a sexual object (Dahal et al, 2015). Participating in a healthy working environment after being trafficked ‘reclaims the experience of work and turns it into an experience of self-sufficiency and accomplishment’ for survivors (Brennan, 2014: 164).…”
Section: Approach To Core Skills Developmentmentioning
confidence: 99%
“…Factors which support the process of (re)integration are family support, increased autonomy, resilience, and independence (although it should be noted these factors were more relevant for women that chose to leave their village of origin and settle in Kathmandu). Overall, stigma and social discrimination by the family and community are overwhelmingly distinguished as some of the primary challenges to (re)integration of women who have been trafficked for sexual exploitation (Gjermeni et al, 2008;Brunovskis and Surtees, 2012;Gan et al, 2014;Da-hal et al, 2015). Additional factors identified as influencing the (re)integration process are financial instability and lack of economic and job opportunities, as well as health and mental problems (Gan et al, 2014).…”
Section: Existing Literaturementioning
confidence: 99%
“…For families or communities where extramarital or same-sex sexual activity is considered taboo (regardless of abusive context), the victim/survivor may be deemed punishable by ostracisation, abandonment, violence, denial of future marriage or even death. 42 Such complexities can lead to frustration or misunderstandings if children respond in unexpected ways to actions designed to help them. High numbers (27%) of potential trafficking victims go missing from care, particularly in the first 48 hours, many of whom are never found.…”
Section: Grooming For Exploitationmentioning
confidence: 99%